PENGARUH LATIHAN SMALL SIDED GAME TERHADAP KEMAMPUAN PASSING MENDATAR PADA TIM FUTSAL THALITA FC PEKANBARU - Pangestu, Rizki; ', Slamet; Juita, Ardiah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Â Â Â Â Â Â Â  Â Â Â Â  Abstrak: The problem of research is ability of passing in futsal team of Thalita Fc Pekanbaru still far excpectation, so when their passing not right on target desired. It can be seen from try out and frendly match even more a big match and this is one of the factory why they loss. This researh was done at futsal team of Thalita Fc Pekanbaru. This researh used Experiment design to see the effect of using â€Small Side Gameâ€. The purpose of the research was to see the effect of using Small Sided Game toward the ability of passing in futsal team at Thalita Fc Pekanbaru. The population of this research was futsal team player of Thalita Fc Pekanbaru district totaling 12 people. Exercise in this study is small sided game. The sampling technique used the total sampling, which was all the population had become the sample. The technique of collecting data was gotten from pre-test and post-test. The instrumen of the research was a ShortÂ Pass testÂ / kicking the ball as a media to measure the ability ofÂ Passing. The data analyzed by using T-test. Based on the data analysis, it can be seen from Tcount was 3,854 and Ttabel 1,796. it meant Tcount > Ttabel with the significant a=0,05. It can be concluded that there is significant effect of exercise small sided game exercise toward horizontal passing ability in Thalita Futsal Team FC Pekanbaru.Â Key Words: Small Sided Games, The Ability Passing, Futsal